Parks, Peace, and Partnership Global Initiatives in Transboundary Conservation - Quinn, Michael S.; Broberg, Len; Freimund, Wayne (Energy, Ecology, and the Environment, 2012)
Today, over 3,000 protected areas around the world contribute to the protection of biodiversity, peaceful relations between neighbouring countries, and the well-being of people living in and around the protected environs. Historical and geo-political constraints are disappearing in a new spirit of collaboration to address common issues confronting ecosystems, species, and communities. Managing across boundaries is seen as the only way to ensure the long-term viability of ecological systems and sustainable communities. Current international thinking in this area is reflected in this collection of essays by park managers, biologists, scholars, scientists, and researchers. From Waterton-Glacier International Park to the European Alps, and Lake Titicaca in Peru and Bolivia, the essays provide illustrative examples of the challenges and new solutions that are emerging around the world.